Sexual health literacy and sexual health behaviours among young adults in Ireland - Nolan, Anne; Smyth, Emer (ESRI, 2025)
Adolescence and young adulthood are critical periods in the development of healthy sexual health and relationships, as patterns of behaviour that develop during these life stages shape outcomes throughout the life course. Recent rises in notifications of certain sexually transmitted infections (STIs) among young people in Ireland have raised concerns over the extent to which young people have the skills and information to make healthy choices in relation to their sexual health and wellbeing. In this context, sexual health literacy – i.e., the degree to which individuals have the ability to find, understand and use information and services to inform decisions and actions – is a key protective factor for the prevention of negative sexual health outcomes and for allowing young people to be more in control of their own sexual and reproductive health. In this report, we used data from Cohort ’98 of Growing Up in Ireland, the national longitudinal study of children and young people in Ireland, to examine the factors associated with sexual health literacy among young adults, and how sexual health literacy is associated with sexual health behaviours (i.e., condom and contraception use). The Growing Up in Ireland data on sexual health literacy were collected in 2018 when the young people were 20 years of age, and the measure of sexual health literacy was based on answers to two questions that gauged knowledge of female fertility and STI prevention methods.